Observations of the Intermediate Water Exchange Between the South China Sea and the Pacific Ocean Deduced From Transient Tracer Measurements. Issue 10 (23rd October 2018) - Deng, Hengxiang; Huang, Peng; Tanhua, Toste; Stöven, Tim; Ke, Hongwei; Guo, Weidong; Wang, Weimin; Cai, Minggang
Abstract: The South China Sea (SCS) is the largest semienclosed marginal sea in the western Pacific (WP) and connects to the west Pacific through the Luzon Strait (LU). In this study, we use the observation of transient tracer chlorofluorocarbon‐12 (CFC‐12) to calculate the ventilation time scales of the SCS, LU, and WP. The CFC‐12 and oxygen data are used together to identify the sandwiched structure vertically of the flows across the LU. The CFC‐12 and oxygen distributions reveal a pronounced decrease westward across the LU and a slight decrease southward in the transport of the SCS. The mean age gradient of the salinity minimum ( S min ) water between the WP and the northern SCS could be a consequence of intensive mixing and entrainment of the inflow water from the WP. An expected difference in age between the LU and SSCS is verified to reflect the transit time for the given water layers in the SCS. Thus, a mean transit time of 77 ± 20 years is estimated for the intermediate water in the SCS interior. Plain Language Summary: In this study, we present CFC‐12 data of seawater, which were collected in the South China Sea and western Pacific during September and October 2016. The CFC‐12, together with the oxygen and hydrographic data, are used to provide general picture of tracer distributions and ventilation time scales of the South China Sea, Luzon Strait, and western Pacific. The CFC‐12 and oxygen data are used together as complementary tracers and identify the sandwiched structure vertically of the flows across the Luzon Strait. We calculate the mean ages using the transit time distributions method to quantify the time scale of waters. An expected difference in age between the Luzon Strait and southern South China Sea is verified to reflect the transit time for the given water layers in the South China Sea. Thus, a mean transit time of ~77 years is estimated for the intermediate water in the South China Sea interior. Key Points: The CFC‐12 and oxygen data are used together to identify the sandwiched structure vertically of the flows across the Luzon Strait The ventilation times are estimated for subsurface and intermediate layers in the South China Sea, Luzon Strait, and western Pacific The mean transit time of approximately 77 years is estimated for the core of the intermediate water in the SCS interior